Association with fertility and abundance - Mumbai Archive Project Team (Jio Institute, 2024)
Goddess Gauri is associated with fertility, and the theme of abundance is recreated inside the house, with fruits and floral hangings tied with mango leaves, a symbol of fertility and prosperity.